Mockito essentials : a practical guide to get you up and running with unit testing using Mockito - Acharya, Sujoy (Community experience distilled., 2014)
This book is ideal for developers who have some experience in Java application development as well as some basic knowledge of test doubles and JUnit testing. This book also introduces you to the fundamentals of JUnit testing, test doubles, refactoring legacy code, and writing JUnit tests for GWT and web services.